Novel Affinity Disks for Bovine Serum Albumin Purification - Tuzmen, Nalan; Kalburcu, Tülden; Uygun, Deniz Aktaş; Akgol, Sinan; Denizli, Adil (Applied biochemistry and biotechnology, 2015)
The adsorption characteristics of bovine serum albumin (BSA) onto the supermacroporous poly(hydroxyethylmethacrylate)-Reactive Green 19 [p(HEMA)-RG] cryogel disks have been investigated in this paper. p(HEMA) cryogel disks were prepared by radical polymerization initiated by N,N,N′,N′-tetramethylene diamine (TEMED) and ammonium persulfate (APS) pair in an ice bath. Reactive Green (RG) 19 was covalently attached to the p(HEMA) cryogel disks. These disks were used in BSA adsorption studies to interrogate the effects of pH, initial protein concentration, ionic strength, and temperature. BSA adsorption capacity of the p(HEMA)-RG cryogel disk was significantly improved after the incorporation of RG. Adsorption capacity reached a plateau value at about 0.8 mg/mL at pH 4.0. The amount of adsorbed BSA decreased from 37.7 to 13.9 mg/g with increasing NaCl concentration. The enthalpy of BSA adsorption onto the p(HEMA)-RG cryogel disk was calculated as −58.4 kJ/mol. The adsorption equilibrium isotherm was fitted well by the Freundlich model. BSA was desorbed from cryogel disks (over 90 %) using 0.5 M NaSCN, and the purity of desorbed BSA was confirmed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The experimental results showed that the p(HEMA)-RG cryogel disks have potential for the quick protein separation and purification process.